2001
DOI: 10.1177/002215540104901012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Atrial Natriuretic Peptide and Brain Natriuretic Peptide in Atrial Granules of Rats with Experimental Congestive Heart Failure

Abstract: S U M M A R YThe natriuretic peptides are believed to play an important role in the pathophysiology of congestive heart failure (CHF). We utilized a quantitative cytomorphometric method, using double immunocytochemical labeling, to assess the characteristics of atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP) in atrial granules in an experimental model of rats with CHF induced by aortocaval fistula. Rats with CHF were further divided into decompensated (sodium-retaining) and compensated (so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
1
14
0
1
Order By: Relevance
“…However, these results are not necessarily inconsistent with reported decreases in serum ANF and BNP protein as a result of LVAD support 25 because ANF and BNP are stored in regulated secretory granules and are released on stimulation. 26,27 It would not be surprising that the serum levels of proteins released from the regulated secretory pathway are at best loosely associated with their message levels. Given the extremely variable levels of expression of natriuretic peptides among patients and within regions of the heart, generalizations may not be possible.…”
Section: Discussionmentioning
confidence: 99%
“…However, these results are not necessarily inconsistent with reported decreases in serum ANF and BNP protein as a result of LVAD support 25 because ANF and BNP are stored in regulated secretory granules and are released on stimulation. 26,27 It would not be surprising that the serum levels of proteins released from the regulated secretory pathway are at best loosely associated with their message levels. Given the extremely variable levels of expression of natriuretic peptides among patients and within regions of the heart, generalizations may not be possible.…”
Section: Discussionmentioning
confidence: 99%
“…Hoffman et al [6] demonstrated that rats ACF have high levels of BNP in the plasma. Similarly, the enhanced plasma levels of BNP coincides with overexpression of BNP in the myocardium of rats with ACF [128], corresponding with the high volume overload and cardiac hypertrophy characterizing this model of CHF.…”
Section: Cardiac Manifestationmentioning
confidence: 99%
“…By contrast, certain neurohormone‐ or hormone‐secreting cells contain small granules of a wider range of sizes (volume = 0.004–0.065 μm 3 ) and the individual granules comprise one to a few unit granules [32, 33]. This may facilitate the simultaneous secretion of a single type of small peptide hormone together with proportional amounts of other secretory products which can have autocrine, paracrine or systemic effects; in such cells, there also would be some membrane conservation during formation of mature granules.…”
Section: Functional Implicationsmentioning
confidence: 99%